Falls in older people at home and leisure time during the COVID-19 pandemic in Portugal. (20th October 2021) - Alves, T; Rodrigues, E; Neto, M; Mexia, R; Matias-Dias, C
Abstract:  : Falls are one of the most common mechanisms of injury namely at home and in leisure time reaching one of the most vulnerable groups of the population such as the older ones, with expression in morbidity and mortality. The pandemic context we are experiencing it has had effects on the physical, mental and social wellbeing of populations but also on the use of health care whose magnitude and reasons are subject of discussion. The aim of this study is to understand the evolution of falls episodes in victims aged 65 and over, which needed attendance in the emergency room of the Health National Service Hospitals in Portugal based on hospital records, through EVITA system, between 2017 and 2020. A descriptive analysis of the data was performed, with the determination of absolute and relative frequencies (percentages). Bivariate comparisons were performed using Pearson's chi-square test with a significance level of 5%. In this analysis, the statistical program SPSS V.24 was used. In the four years between 2017 and 2020 the older people aged 65 and over represented 27% of the total of attendances in the emergency room. Considering the total of ED attendances in this age group 10% occurred due to fall at home or during leisure time. In the last four years there were 462 953 falls in people victims aged 65+, constituting 46% of hospital ED attendances by fall. From march to december 2020, falls episodes have remained below the values of similar periods in the previous four years (p < 0, 01). The largest percentage decrease in falls in 2020 compared to the same period in 2019 occurred in april, with a decrease of 41%. Most of this falls in the study population occurred at home (61%), followed by falls in outdoor spaces (11%). Globally, this reality regarding to the decrease of the ED attendances during this pandemic context is not exclusive to Portugal. Key messages: The older people represented 27% of the total of attendances in the emergency room in the four years in analysis. 10% of ED attendances occurred due to fall at home or during leisure time. From march to december 2020, was observed a significant decrease of falls episodes compared with the previous four years.